S16: Advancing the Implementation of Physical Activity Into Specialist Mental Health Services (Baltic Journal of Sport and Health Sciences, 2026)
Robust evidence now exists supporting the use of physical activity as an effective powerful therapeutic option for people accessing specialist mental health services (Maurus et al., 2024). In the context of physical, cognitive, and mental health benefits, there appears an urgent need to implement and expand physical activity opportunities within mental health services across various contexts (Deenik et al., 2019; Stubbs et al., 2024). However, while some contexts have advanced service provision in this regard, many other European contexts provide physical activity in an ad hoc and insufficient manner (Machaczek et al., 2023). Thus, there is scope for research to better understand current physical activity provision and to advance the knowledge on successful implementation and scale-up. This symposium will highlight contemporary research on the implementation and value of integrated physical activity for specialist mental health services across the European context. Chermaine Noortman (The Netherlands) will discuss the personal benefits, potential economic value, and implementation learning from a multicomponent lifestyle intervention in the outpatient mental healthcare setting. Megan Cooney (Ireland) will present an overview of the current state of physical activity provision in an international context, and also detail a case study of a model of novel integrated physical activity in Irish mental health services. Florence Kinnafick (UK) will share findings from international consensus research utilising the Nominal Groups Technique, focusing on implementation strategies specific to inpatient settings. Katarzyna Karolina Machaczek (UK) will offer insights into supporting the long-term maintenance of physical activity for people who live with severe mental ill health, including the voice of lived experience.Taken together, this symposium aims to provide novel insights and build a picture of how we can all work together to implement integrated physical activity interventions to improve physical and mental health outcomes for people who access specialist mental health services.